2020
DOI: 10.29333/pr/8235
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Psychological Well-Being and Stress: A Cross-Cultural Perspective on Psychological Well-Being and Gender Differences in a Population of Teachers

Abstract: The goal of the present study is to examine mainly the associations of contextual variables with stress and teachers' psychological well-being across organizational cultures. The responses (N= 51,782) of a population of primary school teachers from 15 different educational cultures were analyzed. Structural equation modeling (SEM) was implemented to confirm the associations of protective factors with stress and workplace well-being at the individual unit of analysis. Following the individual-level analysis, mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 39 publications
(77 reference statements)
2
17
0
3
Order By: Relevance
“…In addition, the results show that the heritage cultural orientation (not the national cultural orientation) has significant correlation with the psychological adjustment of the Bangladeshi ethnic youth regardless of gender. This finding is consisted with some findings which showed strong relationships between psychological wellbeing and heritage cultural values (Cauce & Domenech-Rodriguez, 2002;Katsantonis, 2020;Priest et al, 2016). The most likely reason for this positive relationship is the fact that individuals who have positive attitude toward their heritage culture are likely to get family support to integrate the heritage culture values with the national culture values (Perez-Brena et al, 2018), and they tend to make better adjustment in a bicultural or multicultural environment, especially when the family emphasizes the ethnic-racial socialization of its members (Nguyen et al, 2015).…”
Section: Discussionsupporting
confidence: 80%
“…In addition, the results show that the heritage cultural orientation (not the national cultural orientation) has significant correlation with the psychological adjustment of the Bangladeshi ethnic youth regardless of gender. This finding is consisted with some findings which showed strong relationships between psychological wellbeing and heritage cultural values (Cauce & Domenech-Rodriguez, 2002;Katsantonis, 2020;Priest et al, 2016). The most likely reason for this positive relationship is the fact that individuals who have positive attitude toward their heritage culture are likely to get family support to integrate the heritage culture values with the national culture values (Perez-Brena et al, 2018), and they tend to make better adjustment in a bicultural or multicultural environment, especially when the family emphasizes the ethnic-racial socialization of its members (Nguyen et al, 2015).…”
Section: Discussionsupporting
confidence: 80%
“…In contrast, African, South America and Oceanian studies represented 6%, 1% and 4%, respectively, as shown in Figure 2 . One study [ 39 ] was conducted across multiple continents.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the possibility to apply the alignment method, when the assumption of strong measurement equivalence is not tenable, this means that cross-cultural differences exist. Additionally, this indicates a differential additive response style and that other factors beyond the latent variable of interest (i.e., bullying) exert an effect on what options of this scale the respondents endorse (Katsantonis, 2020;Kline, 2016). The next step after strong measurement non-equivalence would be to identify some culture-related variables that may influence the scores on the non-equivalent measure to explain cross-cultural differences (Poortinga et al, 2002).…”
Section: The Issue Of Measurement Equivalence In Cross-cultural Educational Researchmentioning
confidence: 99%